I Integrasi Antara Etika Bisnis dan Pemasaran Syariah Dalam Meningkatkan Kepuasan Pelanggan Di Toko Al-Bugisiyyah Collection Makassar - Jamaal, Rosmah; Efendi, Ahmad (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2025)
Islamic marketing ethics focuses on the principles of equality, justice, and value maximization for the welfare of society. These ethics play a crucial role in raising the standard of customer behavior. The customer-centric strategy is now considered an important element due to the rapidly changing marketing trends in MSMEs, especially in the Al-Bugisiyyah Collection. Therefore, the purpose of this study is to find out the important role of Islamic marketing ethics and identify its influence on customer satisfaction in Al-Bugisiyyah Collectin stores. This study uses a qualitative descriptive method with a case study approach. Data is collected through observations, in-depth interviews with owners and customers, and internal store documentation. The results of the study show that consistent Islamic marketing ethics play a very important role in increasing customer satisfaction and loyalty and can increase repeat orders. These findings reinforce the importance of a value approach in Muslim retail businesses to build long-term relationships with customers